Ribosomal stalling during translation: providing substrates for ribosome-associated protein quality control - Joazeiro, Claudio A. P. (Annual review of cell and developmental biology, 2017)
Cells of all organisms survey problems during translation elongation, which may happen as a consequence of mRNA aberrations, inefficient decoding, or other sources. In eukaryotes, ribosome-associated quality control (RQC) senses elongation-stalled ribosomes and promotes dissociation of ribosomal subunits. This so-called ribosomal rescue releases the mRNA for degradation and allows 40S subunits to be recycled for new rounds of translation. However, the nascent polypeptide chains remain linked to tRNA and associated with the rescued 60S subunits. As a final critical step in this pathway, the Ltn1/Listerin E3 ligase subunit of the RQC complex (RQCc) ubiquitylates the nascent chain, which promotes clearance of the 60S subunit while simultaneously marking the nascent chain for elimination. Here we review the ribosomal stalling and rescue steps upstream of the RQCc, where one witnesses intersection with cellular machineries implicated in translation elongation, translation termination, ribosomal subunit recycling, and mRNA quality control. We emphasize both recent progress and future directions in this area, as well as examples linking ribosomal rescue with the production of Ltn1-RQCc substrates.